Ladybug Girl at the Beach - Soman, David; Davis, Jacky 1966- (New York : Dial Books for Young Readers, 2010)
Lulu, who likes to wear a ladybug costume, goes to the beach for the first time and makes sand castles, flies kites, and deals with her fear of the ocean.
Keywords: Beaches -- Fiction; Fear -- Fiction